Ti(III)-Mediated Radical-Induced Approach to a Bicyclic δ-Lactone with a Bridgehead β-Hydroxy Group - Das, Dipendu; Khan, Hina P. A.; Chakraborty, Tushar Kanti (Synthesis, 2018)
Herein, we portray a synthetic route to a bicyclic lactone containing a bridgehead hydroxy group, a structure that is present in many natural products of biological and medicinal relevance. Ethyl (E)-3-(dimethylphenylsilyl)-7,8-epoxyoct-2-enoate underwent radical-mediated reductive epoxide opening with concomitant intramolecular cyclization using Cp2Ti(III)Cl to give cis-6-(dimethylphenylsilyl)-3-oxabicyclo[4.3.0]nonan-4-one, a bicyclic lactone with a bridgehead silyl group serving as a masked hydroxy group. Furthermore, the bridgehead C–Si bond underwent stereoretentive oxidative cleavage to give cis-6-hydroxy-3-oxabicyclo[4.3.0]nonan-4-one in high yield under Tamao–Fleming oxidation conditions; this demonstrates the potential utility of this strategy in the synthesis of many natural products bearing similar hydroxylated bridgehead chiral center embedded in a bicyclic lactone framework.
Keywords: quaternary center; bridgehead hydroxy; Cp2TiCl; bicyclic lactone; radical cyclization; Tamao–Fleming oxidation